Dispute settlement under the UNCLOS with special reference to compulsory procedures: an appraisal - Islam, Md. Asraful; Paripurna, Amira; Islam, Md. Zahidul (Asian and African Research Centre, 2021)
This paper examines the dispute settlement mechanism under the United Nations Convention on the Law of the Sea (UNCLOS), 1982 specially highlighting the compulsory procedures entailing binding decisions. The purpose of this study is to evaluate the applicability and effectiveness of the dispute settlement provisions of the UNCLOS. The study uses a legal and doctrinal research methodology followed by an analytical approach. In identifying and interpreting data, both primary and secondary legal sources are considered. The study finds that the dispute settlement mechanism of the UNCLOS is unique, flexible, user friendly and equally effective, although there are some limitations and exceptions to the compulsory procedures set out by the Convention itself. Hence, it is concluded that the state parties to the Third UN Conference on the law of the Sea did absolutely the right thing incorporating the dispute settlement mechanism in the Convention itself rather than doing the same in an optional protocol, thus making the Convention comprehensive and exhaustive among the global powers.